2007
DOI: 10.1186/1476-5926-6-4
|View full text |Cite
|
Sign up to set email alerts
|

CIDE-A is expressed in liver of old mice and in type 2 diabetic mouse liver exhibiting steatosis

Abstract: Background: Increased levels of circulating fatty acids caused by insulin resistance and increased adipocyte lipolysis can accumulate within the liver resulting in steatosis. This steatosis sensitizes the liver to inflammation and further injury which can lead to liver dysfunction. We performed microarray analysis on normal mouse liver tissue at different ages and type 2 diabetic liver exhibiting steatosis to identify differentially expressed genes involved in lipid accumulation and liver dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 42 publications
2
24
0
Order By: Relevance
“…No difference in FSP27 or CIDEA transcript level was detected for wild-type vs. ob/ob kidney, nor did we detect CIDEA in either wild-type or ob/ob adipose tissue (data not shown). The upregulation of CIDEA in ob/ob liver is in line with the finding by Kelder et al (22) of enhanced expression of CIDEA in the liver of aged or type 2 diabetic mice exhibiting steatosis. It has also been reported that CIDEA is markedly induced in liver via activation of PPAR␥ and PPAR␣ transcription factors, which interact with their cognate PPREs in the CIDEA 5Ј-flanking region (58).…”
Section: Fsp27 Transcript Level Is Under Tight Regulation By Insulin supporting
confidence: 78%
“…No difference in FSP27 or CIDEA transcript level was detected for wild-type vs. ob/ob kidney, nor did we detect CIDEA in either wild-type or ob/ob adipose tissue (data not shown). The upregulation of CIDEA in ob/ob liver is in line with the finding by Kelder et al (22) of enhanced expression of CIDEA in the liver of aged or type 2 diabetic mice exhibiting steatosis. It has also been reported that CIDEA is markedly induced in liver via activation of PPAR␥ and PPAR␣ transcription factors, which interact with their cognate PPREs in the CIDEA 5Ј-flanking region (58).…”
Section: Fsp27 Transcript Level Is Under Tight Regulation By Insulin supporting
confidence: 78%
“…Although FSP27 is generally expressed in adipocytes, high levels are also observed in steatotic livers (31,48; data not shown), suggesting a causative role in hepatic lipid accumulation. Cidea and adipophilin are also highly expressed in steatotic liver (4,34,40,50,51) where they as well as Cideb are involved in hepatic lipid accumulation (4, 49, 52); however, additional experiments are required to test a role for FSP27 in hepatic steatosis.…”
Section: Journal Of Biological Chemistry 14363mentioning
confidence: 99%
“…Other members of the CIDE family, Cidea and Cideb, influence metabolism and whole body lipid homeostasis (3)(4)(5)34). To investigate effects of FSP27 deficiency on metabolic variables in adipocytes, we measured basal and stimulated glucose uptake and lipolysis.…”
Section: Fsp27 Deficiency In 3t3-l1 Adipocytes Inhibits Formation Of mentioning
confidence: 99%
“…Expression of NF-kB with age is consistent with elevated levels of inflammatory markers and a proinflammatory phenotype. Cytokines and chemokine profiles, likely activated by NF-kB, have been observed in gene expression studies of both human and animal tissues including brain [67], lung [5], liver [54], cartilage [53], and coronary arteries [25]. In fact, a review of gene expressions of nine tissue types in mice and humans revealed that the occurrence of the NF-kB motif was most ubiquitous and strongly associated with age [2].…”
Section: Nf-kb Feedback and Inflammationmentioning
confidence: 95%